2006
DOI: 10.1021/ie050952j
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and Acetaldehyde Production by Selective Oxidation of Ethanol Using Mesoporous V−MCM-41 Catalysts

Abstract: Vanadium-incorporated MCM-41 type catalytic materials, which were synthesized by a direct hydrothermal synthesis procedure, showed very high activity and high selectivity in the production of ethylene from ethanol in an oxidative process. Ethylene selectivity showed a significant increase with an increase in temperature over 300 °C, while relatively high acetaldehyde selectivities were observed at lower temperatures. An ethylene yield value of 0.66 obtained at 400 °C with an O2/ethanol feed ratio of 0.5 was be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 44 publications
3
55
0
Order By: Relevance
“…[1] An example of this is the increased need for ethylene, a major precursor for the pharmaceutical and polymer industries. Currently ethylene is produced from steam cracking of fossil fuels, requiring temperatures exceeding 700 o C. [2] However, finite reserves of fossil fuels or shale gas cannot solely sustain such growth indefinitely, [3] inspiring the search for novel precursors. In contrast, biomass-based precursors are considered viable long term options, with bio-ethanol, fermented from sugars, being considered as an alternative feedstock in ethylene production ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1] An example of this is the increased need for ethylene, a major precursor for the pharmaceutical and polymer industries. Currently ethylene is produced from steam cracking of fossil fuels, requiring temperatures exceeding 700 o C. [2] However, finite reserves of fossil fuels or shale gas cannot solely sustain such growth indefinitely, [3] inspiring the search for novel precursors. In contrast, biomass-based precursors are considered viable long term options, with bio-ethanol, fermented from sugars, being considered as an alternative feedstock in ethylene production ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…9 There have been a number of studies, as well, on the activity of supported vanadia for the oxidative dehydrogenation (ODH) of ethanol to acetaldehyde [10][11][12][13][14][15][16][17][18][19] or acetic acid. 20 These studies have shown that the catalyst activity depends on the nature of the support, and that higher rates are achieved with supports such as Al 2 O 3 , Al 2 O 3 -ZrO 2 , TiO 2 , TiO 2 /SiO 2 , and ZrO 2 -SiO 2 than with SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in view of the energy crisis, the production of ethylene from ethanol has received widespread attention in recent years [1][2][3][4][5], as ethanol can be obtained easily from renewable biomass by fermentation.…”
Section: Introductionmentioning
confidence: 99%